Language of Saptariya Tharu - Chaudhary, Mahesh Kumar (Researcher: A Research Journal of Culture and Society, 2014)
The purpose of this paper is to present a general overview of the Tharu language as it is spoken in Saptari District. Geographical distribution of Tharu, its genetic affiliation, linguistics characteristics; phonology, morphology and syntax are looked into brief. This paper is based mainly on primary sources along with secondary one. DOI: http://dx.doi.org/10.3126/researcher.v1i2.9885 Researcher 1(2) 2013: 49-62